Risk Management and Financial Performance of Manufacturing Firms in Nigeria - Akinleye, Gideon Tayo; Olanipekun, Comfort Temidayo (Financial Risk and Management Reviews, 2021)
The current study investigated risk management and financial performance of manufacturing firms. Specifically, the study analyzed liquidity risk and market risk effect on after tax profit of manufacturing establishment in Nigeria. The study employed panel data over the period spanning from 2010-2019 across 10 firms. Secondary data were gathered through the annual reports of the selected firms. Correlation analysis and panel-based estimation techniques were used. The outcome showed that liquidity risk positively and significantly affect profit after tax while market risk (measured by interest rate risk) negatively and insignificantly affect profit after tax of sampled firms quoted in Nigeria. This study concluded that efficient and effective risk management will positively affect performance of quoted firms in Nigeria, most specially management of internal risk such as the liquidity risk. Hence, firms should build an internal control system flexible in nature to harness the benefit of internal risk management and also normalize the negative effect of external risk such as the interest rate on performance.